Feminist Discourse and Motherhood Issue: An Analytic Theoritical Study - Fattah, Media I. (KOYA UNIVERSITY JOURNAL OF HUMANITIES AND SOCIAL SCIENCES, 2024)
The study addresses the issue of motherhood in the discourse of the three waves of feminism, which view motherhood as a key factor in women’s oppression, likening it to slavery that confines their existence to childbirth and child-rearing. The first wave proposed rejecting motherhood as a solution to the oppression that deprives women of their freedom to work and achieve self-realization. The second wave advocated for the right to abortion as an alternative to motherhood, which restricts women’s professional and social freedoms. The radical wave took a bolder stance, emphasizing a woman’s right to choose motherhood if desired. However, since the social relationship tied to motherhood might undermine her autonomy, it suggested artificial insemination as a technological alternative, enabling motherhood without the constraints of a marital relationship. The study aims to explore feminist perspectives on motherhood and their impact on Kurdish women. Feminist ideologies have significantly shaped women’s social awareness globally, including Kurdish women, who increasingly view motherhood as an issue requiring pragmatic solutions. Findings reveal that the influence of feminist alternatives varies based on social contexts and Kurdish women’s ability to adopt them, particularly as some proposals conflict with Kurdish religious and cultural values. As a result, women often opt for alternatives more aligned with societal norms, such as family planning, secret abortions, or avoiding alternatives due to religious, social, or psychological factors. Despite the difficulties of motherhood as a social and gender role, it is still a high value and is considered a high social position in Kurdish society.